Cancer Incidence in Systemic Sclerosis: Meta‐Analysis of Population‐Based Cohort Studies. Issue 7 (2nd July 2013) - Onishi, Akira; Sugiyama, Daisuke; Kumagai, Shunichi; Morinobu, Akio
<x xml:space="preserve">Abstract</x> Objective To examine cancer incidence in patients with systemic sclerosis (SSc) through a meta‐analysis of population‐based cohort studies. Methods Five different databases (Medline, Scopus, CINAHL [Cumulative Index to Nursing and Allied Health Literature], Web of Science, and Cochrane Collaboration) were searched for articles published between January 1966 and May 2012; review articles and the reference lists from the articles that resulted from the search were also evaluated. Population‐based cohort studies with data relevant to the determination of cancer risk in patients with SSc were included. All articles that met strict inclusion criteria were analyzed for data on population size, time of followup, and observed‐to‐expected cancer ratios, also known as standardized incidence ratios (SIRs). Results Six articles met criteria and were included in the meta‐analysis. The pooled SIR for the incidence of cancer overall was 1.41 (95% confidence interval [95% CI] 1.18–1.68), and significant heterogeneity was observed as a consequence of variability in the participants, outcome, study design, and risk of bias among the studies. Men had a significantly higher pooled SIR (1.85 [95% CI 1.49–2.31]) than women (SIR 1.33 [95% CI 1.18–1.49]) (P < 0.01), and stratification for sex eliminated heterogeneity, which indicates that variability among the studies greatly contributed to differences between the sexes. There were no differences between limited cutaneous SSc and diffuse cutaneous SSc (P = 0.77). Significant increases were observed in the risk of cancer of the lung, liver, hematologic system, and bladder, as well as of non‐Hodgkin's lymphoma and leukemia. Conclusion SSc is associated with an increased risk of cancer, particularly lung, liver, hematologic, and bladder cancers, although absolute risk is relatively low. Men with SSc have a higher risk of developing cancer than women.